The Role of Imaging In The Diagnosis of Pulmonary Embolism - Alfian Nur Rosyid; M. Yamin; Arina Dery Puspitasari (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Pulmonary embolism is a common condition and sometimes can be life-threatening. A proper diagnosis can reduce mortality. Some examinations are needed to diagnose pulmonary embolism, including assessing the risk factors, clinical examination, D-dimer tests, and imaging. Imaging is necessary when the previous assessment requires further investigation. There are more imaging that can be used to diagnose and assess the severity of pulmonary embolism. However, it is still controversial regarding imaging modalities for optimizing pulmonary embolism diagnose. Chest X-Ray cannot exclude pulmonary embolism, but it is needed to guide the next examinations and to find alternative diagnoses. Pulmonary Multi-Detector CT Angiography is the gold standard to diagnose pulmonary embolism.